PEMBELAJARAN BAHASA BERBASIS LINGKUNGAN SEBAGAI UPAYA MEMBANGUN KECERDASAN EKOLOGIS - Tulalessy, Quin Donspri (Universitas Papua Manokwari, 2016)
The paper gives a conditional understanding about the importance of environmental-based learning to establish ecological intelligence. Environmental-based anguage learning is an effort to increase knowledge and understanding aiming at giving critical understanding to the community learners in order to build ecological intelligence for human sake.Environmental preservation effort through the texts in language learning representatively gives a picture of how rich human knowledge about the nature is. Thus, it is worth that through formal and non-formal education which are the basis for intellectual community, environmental-based learning is integrated in language learning. This is reasonable since it is suitable with the government of West Papua Province programs which is promoted as Conservation Province.Therefore, environmental-based language learning could help the learners to acquire language learning and also to build human intellegential construction in interacting with the nature for their future life. Education is the place where humans are formed to obtain any information which is useful for shapping and establishing human cognitve infrastructure regarding many things. One of them is ecology (environment/nature).